Study design, result reporting and publication of late-stage cardiovascular trials. (25th November 2020) - Kapelios, C; Naci, H; Vardas, P; Mossialos, E
Abstract: Introduction: Preregistration of study protocols in publicly accessible databases is required for publication of study results in high-impact medical journals. Nonetheless, data on the characteristics of clinical trials registered in these databases and their outcome, in terms of result reporting and publication are limited. Methods: The purpose of this study was to perform a comprehensive analysis of the characteristics of late-stage, cardiovascular disease (CVD) trials registered in Clinicaltrials.gov. We searched for interventional, late-phase (annotated as phase III) CVD studies in adults first posted after 1/1/2013 and completed up to 31/12/2018. Data on study design, result reporting, result spinning and publication were collected, and potential associations with a pre-defined set of explanatory factors were examined. Results: The search yielded 352 studies. One hundred were excluded from further analysis because they were misclassified as CVD studies, while 2 were excluded as duplicate entries. In total, 250 CVD trials were included in the analysis. The most commonly studied fields were hypertension, coronary artery disease and heart failure. Of these, 193 (77.2%) were randomized studies, 99 (39.6%) open label designs, and 126 (50.4%) had industry as main sponsor. 179 trials (71.6%) evaluated the effect of drugs and 27 (10.8%) evaluated devices. Industry-funded trials focused on patent-protected drugs and devices more often than non-industry-funded trials (72.0% vs. 30.6%, P<0.001 and 55.0% vs. 26.3%, P=0.033, respectively). Sixty three studies (25.2%) had results posted on clinicaltrials.gov, and 116 (46.4%) had results published in the scientific literature. No clear indication of result spinning was found in 96 (85%) of published studies. In multivariate analysis, industry sponsorship was statistically significantly associated with results posting (OR: 3.56; 95% CI:1.67–7.60, P=0.001) and publication (OR: 0.41; 95% CI:0.23–0.75, P=0.004). Results spinning was associated with confirmation of the primary hypothesis (OR: 0.23; 95% CI: 0.07–0.75, P=0.015) and results posting (OR: 0.08; 95% CI: 0.01–0.65, P=0.018). Conclusions: Among late-stage cardiovascular trials only 1/4 had their results posted on clinicaltrials.gov and less than half had results published. Industry sponsors were more likely to invest in research on patent-protected drugs and devices than were non-industry sponsors. Having industry as a sponsor was independently associated with increased likelihood of results posting, but decreased likelihood of results publication. Results reporting was significantly associated with lower risk of results spinning. Funding Acknowledgement: Type of funding source: None